2004
DOI: 10.1212/01.wnl.0000134881.82983.be
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric freezing of gait in hemiparkinsonism-hemiatrophy

Abstract: A 62-year-old man presented with a 2-year history of dyskinesia and a 10-month history of gait difficulty. He had developed circumferential gait of the left leg at the age of 40 years. About 2 years later, he experienced slowness and stiffness with dystonic posturing of the left hand. When examined he had a mild left hemifacial and hand atrophy. There was marked rigidity, bradykinesia, and a 4 -6 Hz resting tremor in the left extremities. When he walked, he had circumduction of the left leg with ankle inversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…29 A similar case associated with asymmetric freezing has been reported previously in a patient with HPHA. 30 Seven patients had brisk reflexes with extensor plantar response on the side of HA. The presence of pyramidal tract signs has been consistently noted in other reported cases of HPHA.…”
Section: Discussionmentioning
confidence: 96%
“…29 A similar case associated with asymmetric freezing has been reported previously in a patient with HPHA. 30 Seven patients had brisk reflexes with extensor plantar response on the side of HA. The presence of pyramidal tract signs has been consistently noted in other reported cases of HPHA.…”
Section: Discussionmentioning
confidence: 96%
“…A reduction in spasticity may improve symmetry of upper limb movements [26]. Reduced arm-swing, which can be asymmetrical, is also a typical feature of Parkinson's disease [27,28]. Wood and coworkers demonstrated that either unilateral or bilateral reduction of arm-swing is a predictor of falling in Parkinson patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…Although lower extremity asymmetry during gait has been well quantified in individuals with PD,4,14-16 the arm swing asymmetry during walking has only been described qualitatively. 1,6,17 For this reason, the present work focused on arm swing magnitude, and its side-to-side asymmetry, during gait in individuals with early PD. Based on previous descriptions of altered shoulder motion,4,7-9 and the asymmetric onset of motor symptoms,11,12 we hypothesized that arm swing in individuals with early PD would be decreased in amplitude and more asymmetric when compared to controls.…”
mentioning
confidence: 99%